2022
DOI: 10.1021/acs.iecr.1c03836
|View full text |Cite
|
Sign up to set email alerts
|

Organic Electro-Optics and Optical Rectification: From Mesoscale to Nanoscale Hybrid Devices and Chip-Scale Integration of Electronics and Photonics

Abstract: The performance of electro-optic devices based on organic second order NLO materials has been improved by orders of magnitude through theory-guided improvement in the electrooptic activity and other relevant properties of organic materials and by field compression of radio frequency (RF) and optical fields associated with the transition from microscale/mesoscale devices to silicon−organic hybrid (SOH) and plasmonic−organic hybrid (POH) devices with nanoscopic dimensions. This paradigm shift in organic electro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 205 publications
0
11
0
Order By: Relevance
“…For further enhancements, especially in the narrowest of slot width devices, it may be necessary to incorporate surface modifiers such as self-assembled monolayers, or even replace poling with sequential synthesis of acetic superlattices. [22] For bulk film devices, spin coating of micrometer-thick films is the standard method of depositing the OEO material. For nanophotonic devices film thickness of just ~250-500 nm are required, necessitating minor process re-optimization.…”
Section: Process Developmentmentioning
confidence: 99%
“…For further enhancements, especially in the narrowest of slot width devices, it may be necessary to incorporate surface modifiers such as self-assembled monolayers, or even replace poling with sequential synthesis of acetic superlattices. [22] For bulk film devices, spin coating of micrometer-thick films is the standard method of depositing the OEO material. For nanophotonic devices film thickness of just ~250-500 nm are required, necessitating minor process re-optimization.…”
Section: Process Developmentmentioning
confidence: 99%
“…7,8 Recent research had using CLD type organic second-order nonlinear chromophore to prepare 500 GHz electro-optic modulator, 9,10 terahertz field detector 11,12 , plasmonic device [13][14][15] and other optoelectronic devices. 16,17 All of these indicate that the organic second-order nonlinear chromophores have broad practical prospects.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Recently, CLD-type organic secondorder nonlinear chromophores have been used to prepare 500 GHz electro-optic modulators, 9,10 terahertz eld detectors, 11,12 plasmonic devices [13][14][15] and other optoelectronic devices. 16,17 All of these indicate that organic second-order nonlinear chromophores have broad practical prospects. However, the practical application of organic electro-optic chromophores still faces many challenges.…”
Section: Introductionmentioning
confidence: 99%
“…20 Cocrystallizing PEO and CNA is an alternative method compared to blending NLO chromophores with amorphous, high T g polymer matrices 24 or crosslinking the material 25 for creating organic electro-optic devices. 26,27 A major hurdle in blending NLO chromophores in polymer matrices is aligning the chromophores noncentrosymmetrically, which is typically done using electric field poling. 24 Thus, in an effort to realize the use of hierarchically ordered semicrystalline block copolymers containing oriented cocrystals confined within nanoscale domains for optical, ferroelectric, and dielectric applications, it is necessary to establish the selfassembly and thermal transitions of polymer/chromophore binary mixtures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although forming the PEO/CNA cocrystal was possible, it was recently revealed that the cocrystal exhibits second-order nonlinear optical (NLO) properties due to the noncentrosymmetric P 1 space group . Cocrystallizing PEO and CNA is an alternative method compared to blending NLO chromophores with amorphous, high T g polymer matrices or crosslinking the material for creating organic electro-optic devices. , A major hurdle in blending NLO chromophores in polymer matrices is aligning the chromophores noncentrosymmetrically, which is typically done using electric field poling …”
Section: Introductionmentioning
confidence: 99%